THE EFFECTIVENESS OF CANCELLING LAND CERTIFICATES THROUGH THE NON-LITIGATION PROCESS - Sitanggang, Pardo; Ahmad, Ahmad (NOMOI Law Review, 2025)
The cancellation of land certificates is an important issue in Indonesia's land system, given the high number of land disputes arising from administrative errors, overlapping rights and abuse of authority. This article examines the effectiveness of non-litigation mechanisms for cancelling certificates by the National Land Agency (BPN) compared with litigation through the courts. The research uses normative legal methods with a statutory and conceptual approach, and examines primary and secondary legal sources. The results of the analysis show that the non-litigation mechanism through the BPN has advantages in terms of time efficiency, cost, and the potential for amicable settlement, especially for administrative cases. However, there are limits to its authority and challenges in maintaining the principle of legality and the protection of community rights. Thus, nonlitigation cancellation of land certificates is effective in administrative contexts, but requires synergy with litigation to resolve complex land conflicts.